Involvement of transmembrane protein 184a during angiogenesis in zebrafish embryos - Field, Cassandra J.; Perez, Alexis M.; Samet, Taryn; Ricles, Victoria; Iovine, M. Kathryn; Lowe-Krentz, Linda J. (Frontiers in Physiology, 2022)
Angiogenesis, the outgrowth of new blood vessels from existing vasculature, is critical during development, tissue formation, and wound healing. In response to vascular endothelial growth factors (VEGFs), endothelial cells are activated to proliferate and move towards the signal, extending the vessel. These events are directed by VEGF-VEGF receptor (Vegfr2) signal transduction, which in turn is modulated by heparan sulfate proteoglycans (HSPGs). HSPGs are glycoproteins covalently attached to HS glycosaminoglycan chains. Transmembrane protein 184a (Tmem184a) has been recently identified as a heparin receptor, which is believed to bind heparan sulfate chains in vivo. Therefore, Tmem184a has the potential to fine-tune interactions between VEGF and HS, modulating Vegfr2-dependent angiogenesis. The function of Tmem184a has been investigated in the regenerating zebrafish caudal fin, but its role has yet to be evaluated during angiogenesis in the developing zebrafish embryo. Here we provide insights into how Tmem184a contributes to the proper formation of the vasculature in embryos. First, we find that knockdown of Tmem184a causes a reduction in the number of intact intersegmental vessels (ISVs) in the zebrafish embryo. This phenotype mimics that of vegfr2b knockout mutants, which have previously been shown to exhibit severe defects in ISV development. We then test the importance of HS interactions by removing the binding domain within the Tmem184a protein, which has a negative effect on angiogenesis. Tmem184a is found to act synergistically with Vegfr2b, indicating that the two gene products function in a common pathway to modulate angiogenesis. Moreover, we find that knockdown of Tmem184a leads to an increase in endothelial cell proliferation but a decrease in the amount of VE-cadherin present. Together, these findings suggest that Tmem184a is necessary for ISVs to organize into mature, complete vessels.